Status of a decennial marine invasion by the bisexual mussel Semimytilus algosus (Gould, 1850) in South Africa. Issue 4 (1st October 2020) - Ma, KCK; McQuaid, CD; Pulfrich, A; Robinson, TB
Abstract : The invasion history and current distribution of the alien marine mussel, the bisexual mussel Semimytilus algosus, on rocky shores of South Africa is described in this study. The eastern edge of its distribution has been monitored since 2014, and the most-recent observations were made between January and March of 2020, at 16 sites between Hondeklipbaai on the west coast and Nature's Valley on the south coast. From these 2020 records, the species ranged across approximately 840 km along the coast, from Hondeklipbaai to Hermanus. The species' invasion history and distribution suggests that this mussel has persisted on the west coast over the past decade, and spread along the coast in both northward and south–southeastward directions. Since 2010, the species has spread predominantly in a southerly and then easterly direction, extending its range by ∼270 km into the Agulhas ecoregion. In contrast, its spread has been slower to the north, with a range extension of only ∼75 km. Long-term, routine monitoring of the coast to track the spread of S. algosus and other invasive marine species, and to identify new incursions, is recommended to support evidence-based management of biological invasions.